2015
DOI: 10.1371/journal.pone.0145550
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Macrophage-Mediated Cell Therapy to Improve Skeletal Muscle Function after Injury

Abstract: Skeletal muscle regeneration following acute injury is a multi-step process involving complex changes in tissue microenvironment. Macrophages (MPs) are one of the key cell types involved in orchestration and modulation of the repair process. Multiple studies highlight the essential role of MPs in the control of the myogenic program and inflammatory response during skeletal muscle regeneration. A variety of MP phenotypes have been identified and characterized in vitro as well as in vivo. As such, MPs hold great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 58 publications
3
50
0
Order By: Relevance
“…We have previously published on the use of polarized mMPs to treat ischemia/reperfusion muscle injury. According to our studies, early delivery of M1 mMPs promotes faster muscle repair [24]. Other reports also showed the benefit of M1 mMPs in accelerating tissue recovery post-injury [25][26][51][52].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We have previously published on the use of polarized mMPs to treat ischemia/reperfusion muscle injury. According to our studies, early delivery of M1 mMPs promotes faster muscle repair [24]. Other reports also showed the benefit of M1 mMPs in accelerating tissue recovery post-injury [25][26][51][52].…”
Section: Discussionsupporting
confidence: 73%
“…The strategy of using cells to elicit complex tissue-specific responses has obvious advantages over the delivery of individual biological factors [23]. We have previously published on the role of inflammatory M1 (LPS/IFN-γ) MPs in skeletal muscle regeneration from ischemia/ reperfusion injury [24]. In addition, Jetten et al [25,26] showed that injection of exogenous, inflammatory M1 MPs and anti-inflammatory M2 MPs had positive effects on reperfusion recovery, concluding that polarization of MPs is sufficient to induce collateral vessel formation.…”
mentioning
confidence: 99%
“…They showed 15% improvements in muscle tension and force 24 h after the activated macrophage infusion. 62 Moreover, they found that the delivery of activated macrophages accelerated myofiber repair and decreased fibrosis 14 days posttreatment. 62 Interestingly, the delivery of unactivated, or resting, macrophages impaired healing of the skeletal muscle.…”
Section: Cell Delivery Of Polarized Macrophagesmentioning
confidence: 99%
“…62 Moreover, they found that the delivery of activated macrophages accelerated myofiber repair and decreased fibrosis 14 days posttreatment. 62 Interestingly, the delivery of unactivated, or resting, macrophages impaired healing of the skeletal muscle. 62 Overall, their data indicate the importance of the initial inflammatory phase to improve healing outcomes, possibly by upregulating an earlier anti-inflammatory phase transition due to a more efficient clearance of apoptotic cells and higher vascularization mediated by activated macrophages.…”
Section: Cell Delivery Of Polarized Macrophagesmentioning
confidence: 99%
“…We found that cyclopamine-treated mice showed a significantly greater proportion of fibers with two or three central nuclei and a higher degree of cell border blurring and cytoplasmic fragmentation, which is a sign of delayed muscle fiber regeneration [23]. In addition, cyclopamine treatment apparently aggravated skeletal muscle fibrosis, which suggested impaired recovery of skeletal muscle function, as increased deposition of connective tissue has a negative impact on contractile muscle function by decreasing myofiber occupancy [32]. Conversely, we also showed that activation of the Shh signaling pathway via exogenous Shh expression decreased muscle destruction and fibrosis.…”
Section: Discussionmentioning
confidence: 99%